Impact of COVID-19 on Primary School Children’s Learning - Apinunmahakul, Amornrat; Mongsawad, Prasopchoke; Sudsawasd, Sasatra (Journal of Applied Economics and Management Strategy, 2023)
This qualitative research aims to investigate learning problems of Thai children, ages 6 to 12 years old, during the school closures due to the COVID-19 pandemic, and to propose feasible solutions to the problems. The research was conducted based on the in-dept interviews of administrators and teachers from 10 schools and a household survey of 3,032 samples with various patterns of living arrangement. The main finding shows that the problem of inequality in education is exacerbated during the pandemic. Even though the inequality does have many facets, the most apparent one is the disparity of household income. To alleviate children’s learning problems during school closures, government’s measures should focus on the accessibility to equipment for online learning. Moreover, the government should consider promoting the use of digital innovations in conjunction with creative medias to develop pleasant online classes for elementary-aged children. Good learning content can draw children’s attention and help them learn effectively.